Who decides? Balancing and Bridging Local, Indigenous and Broader Societal Interests in Canadian Energy Decision-Making. System under stress: Interim report # 1 - Fast, Stewart (Université d'Ottawa | University of Ottawa, 2017)
This report identifies the range of roles for municipal and Indigenous governments in the energy decision-making system as well as concepts for analysis, and recommendations for policymakers and regulators. It builds on the workshop “Who Decides? Balancing and Bridging Local and HigherOrder Interests in Canadian Energy Decision Making” held March 20 and 21, 2017 at the University of Ottawa. This event featured a diverse range of participants from government, Indigenous organizations, industry, ENGOs and academia.
Keywords: Canada; Energy policy; Regulation; Indigenous Rights; Community Engagement; Public Confidence; Social Acceptance; Climate Change